Ekstraksi logam berat dalam air dengan TBP dalam kolom (Mixer-Settler Extraction of Heavy Metals in Aqueous Solution Using TBP in A Mixer-Settler Column) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
This research investigated extraction of heavy metals in aqueous solution using tri buthyl phosphate (TBP) in a mixer settler column. The heavy metals studied in this research were copper (Cu) and lead (Pb). Kerosene was used as a solvent to dilute TBP. The solution containing Cu or Pb was prepared by dissolving CuSO4.51120 or Pb(NO2)2 in aquadest. The mixer settler column used in this experiment was made of acrylic. The mixer diameter was the same as the diameter of settler it was 12 cm. The mixer height was 7.3 cm while the height of settler was 4.7 cm. Drop coalescer was mounted in the middle of mixer and settler separator. The diameter of drop coalescer was 6 cm with the thickness of 1 cm. The holes diameter of drop coalescer was 1 mm. The stirrer used in this experiment was a cross flat blade having 4 cm diameter and 8 mm width impeller. The relationship between the overall volumetric mass transfer coefficient and the influenced variables for a single stage mixer settler is expressed as: CI LanPan 7 PorDi- N C2 or Sh. = K Re.c1Rer2 onaDi2). K (IC D DAB Nan Di Nor The values of constants for the extraction of Cu in aqueous solution are K = 3.41 x 10-", C, = 0.61 and C2 = 1.36. This equation is valid for the range of Reââ = 110.5-511.09 and Re, = 2985.21-7463.01 with the ralative mean arror of 12.85% For the extraction of Pb in aqueous solution, K = 5.86 x 10-9, = 0.67 and C2 = 0.68, and the equation is valid for the range of Reaâ = 110.15-511.09 and Re